A sequential heuristic programming approach for a corrugated box factory: trade-off between set-up cost and trim waste. (12th April 2010) - Zouein, Pierrette; Diab, Jessica
This paper considers a corrugator trim problem for a cardboard boxes manufacturing plant that produces boxes of various sizes servicing known customer demand. We present a suboptimal three-step procedure that minimises both trim waste and setup time cost where setup cost is measured as the loss of production resulting from stock rolls size changes. The procedure leads to the least-cost method of combining customer orders on the corrugator and the optimal roll width to use. The paper concludes by applying the proposed method to derive a lower cost schedule for Unipak, one of the leading manufacturer of cardboard boxes in Lebanon.